MODAL ANALYSIS OF A STRAIGHT PIPE WITH AND WITHOUT FLUID - ISHAK, MIUHAMMAD HARITH IRFAN (IRC, 2020)
This study outlined a simple approach for studying a free vibrational analysis of a straight pipe with different types of support conditions and materials. The normal practices by refineries is that the vibration assessments are only done on the vibrating rotating equipment outlined by standard guidelines. This measurement conducted only gives an equivocal indication of vibratory states of the mechanical rotating equipment ignoring the vibrating pipes near them. The premise of the project is simple which is to investigate the vibrational behaviour that are natural frequencies and mode shapes of the pipes with respect to the pipe length towards the pipe containment, pipe support condition and the materials of the pipe. In the given conditions, the natural frequency and mode shape of the pipe are being discussed thoroughly.